--- title: Chain Rule Introduction --- # Chain Rule Introduction Chain Rule is used to compute the derivative of a composition of functions. Let _F_ be a real valued function which is a composite of two functions _f_ and _g_ i.e. `F(x) = f(g(x))`and both f(x) and g(x) are differentiable. Let the derivative D{F(x)} is denoted as F'(x). By Chain Rule, #### _`F'(x) = f'(g(x)).g'(x)`_ Suppose, g(x) = t then F(x) = f(g(x)) can be rewritten as F(x)=f(t) then in Leibniz's notation Chain Rule can be rewritten as : #### `d(F)/dx = df/dt . dt/dx` ### Example 1. To compute derivative of sin(ax+b) Solution : The function can be visualized as a composite of two functions. F(x)= f(g(x)) t= g(x)= ax+b and f(t)=sin(t) f(t)=sin(t) => df/dt = cos(t) t= g(x) = ax+b => dt/dx = a Now by Chain Rule: d(F)/dx = df/dt . dt/dx => d(F)/dx = a . cost(t) = a.cos(ax+b) OR We can directly apply the formula F'(x) = f'(g(x)).g'(x) = cos(ax+b) . a ## For a function composite of more than two function : Let _F_ be a real valued function which is a composite of four functions _r s t u_ i.e. `F(x)=r(s(t(u(x))))` and all the functions _r(x) s(x) t(x) u(x)_ are differentiable. Let the derivative D{F(x)} is denoted as F'(x). By Chain Rule, #### _`F'(x) = r'(s(t(u(x)))).s'(t(u(x))).t'(u(x)).u'(x)`_ Suppose, a = u(x), b = t(a), c = s(b) then F(x)=r(s(t(u(x)))) can be re-written as F(x)=r(c) then, F(x)=r(c) => d(F)/dx = dr/dc . dc/dx ___ (eqn 1) c = s(b) => dc/dx = ds/db . db/dx ___ (eqn 2) b = t(a) => db/dx = dt/da . da/dx ___ (eqn 3) a = u(x) => da/dx = du/dx ___ (eqn 4) Putting the value of eqn 2 3 4 in eqn 1, we will get : #### `d(F)/dx = dr/dc . ds/db . dt/da . du/dx` ### Example 2. To compute derivative of sin(cos((mx+n)^3)) Solution : The function can be visualized as a composite of four functions. F(x)= r(s(t(u(x)))) where a = u(x) = mx+n b = t(a) = a^3 c = s(b) = cos(b) then F(x)=r(s(t(u(x)))) can be re-written as F(x)= r(c) =sin(c) Now, By chain rule : d(F)/dx = dr/dc . ds/db . dt/da . du/dx => d(F)/dx = cos(c) . -sin(b) . 3a^2 . m => d(F)/dx = cos(cos((mx+n)^3)) . -sin((mx+n)^3)) . 3(mx+n)^2 . m OR We can directly apply the formula, F'(x) = r'(s(t(u(x)))).s'(t(u(x))).t'(u(x)).u'(x) = cos(cos((mx+n)^3)) . -sin((mx+n)^3)) . 3(mx+n)^2 . m